2022
DOI: 10.12659/msm.937640
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Multimodal Chiropractic Care Featuring Spinal Manipulation for Persistent Spinal Pain Syndrome Following Lumbar Spine Surgery: Retrospective Chart Review of 31 Adults in Hong Kong

Abstract: Background The term “persistent spinal pain syndrome type 2” (PSPS-2) has been proposed by the International Association for the Study of Pain to replace the term “failed back surgery syndrome”. This retrospective study aimed to evaluate effectiveness of multimodal care featuring chiropractic spinal manipulation (CSMT) in 31 adults in Hong Kong with PSPS-2. Material/Methods We identified new adult patients with PSPS-2 receiving CSMT from 2016 to 2018. Demographic and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Therefore, we suggest that these treatments should be used cautiously on a case-by-case basis. Certain clinical variables such as patients' age, the length of time since surgery, the presence of neurologic deficits, the type of surgery, the presence of surgical implants, or the number of spinal segments involved in the surgery could be relevant toward influencing a providers' decision to use manual therapy in these patients, or the type of manual therapy used [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that these treatments should be used cautiously on a case-by-case basis. Certain clinical variables such as patients' age, the length of time since surgery, the presence of neurologic deficits, the type of surgery, the presence of surgical implants, or the number of spinal segments involved in the surgery could be relevant toward influencing a providers' decision to use manual therapy in these patients, or the type of manual therapy used [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Chiropractors in Hong Kong utilize manual techniques such as spinal manipulation and soft tissue mobilization to address musculoskeletal dysfunction and reduce pain [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. According to a 2013 survey undertaken by the Census and Statistics Department of the Hong Kong Special Administrative Region, more than half (53.6%) of the 33,700 individuals who received chiropractic care had previously tried other forms of treatment.…”
Section: Chiropractic As An Effective and Low-risk Therapymentioning
confidence: 99%
“…[3] Chiropractors in Hong Kong are legally authorized to diagnose and treat musculoskeletal conditions. As conservative spine specialists and primary care practitioners, numerous studies have reported that chiropractors in Hong Kong provide non-invasive care for prevalent neuromusculoskeletal conditions and injuries [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, their inability to officially certify patients' incapacity limits the utility of chiropractic services.…”
Section: Introductionmentioning
confidence: 99%
“…Radiology services in primary care can reduce needless referrals to specialists and hospitals and optimize healthcare resource use. Primary healthcare practitioners, including general practitioners, nurses, pharmacists, physiotherapists, and chiropractors, can perform many initial diagnostic examinations with direct access to diagnostic imaging services [ 21 , 22 ]. This technique reduces the number of patients referred to specialists and hospitals for diagnostics, relieving secondary and tertiary care facilities.…”
Section: Reviewmentioning
confidence: 99%